Differences in infection patterns of vector-borne blood-stage parasites of sympatric Malagasy primate species (Microcebus murinus, M. ravelobensis). (December 2019) - Klein, Annette; Strube, Christina; Radespiel, Ute; Springer, Andrea; Zimmermann, Elke
Abstract: The dynamic relationship of vector-borne parasites, arthropod vectors and their hosts is prone to change under the influence of climate change, global integration, shifting demographics and deforestation. It is therefore essential to better understand parasitism in wildlife populations, including parasites transmitted by blood-feeding vectors, and explore host range and heterogeneity of parasitic infections. We investigated Giemsa stained blood smears of two sympatric Malagasy primate species ( Microcebus murinus : 184 samples from 69 individuals and M. ravelobensis : 264 samples from 91 individuals) for blood-stage parasites and tested for a potential influence of host species, sex, body mass and sampling month on blood-stage parasite prevalence and infection intensity. No protozoan parasites were detected in either host species. A host-specific difference was observed in filarial nematode infections, with higher risk of infection in M. murinus (prevalence 30.43%), than in M. ravelobensis (prevalence 6.59%), which may be explained by differences in host behavior and/or immune competence, linked to the period of host-parasite coevolution. Neither sex nor sampling month influenced infection prevalence or intensity significantly. We did not observe a negative effect of microfilarial infections on host fitness when taking body mass as a proxy. Our results support the hypothesis of a long-term evolutionary adaptation of hosts and parasites, leading to persistent infection with low morbidity. Morphological and molecular analyses indicate the finding of a new species, " Lemurfilaria lemuris ". Genetic analysis furthermore showed >99% sequence identity with microfilariae described from a sympatric, larger-bodied lemur species of a different genus, suggesting low host-specificity of the detected filariae and pathogen transmission across genus boundaries. Findings contribute to a more comprehensive picture of vector-borne diseases of Malagasy lemurs. Graphical abstract: Image 1 Highlights: Small Malagasy primate species are hosts of the newly described Lemurfilaria lemuris. Risk of microfilarial infection and infection intensity differed between host species. This could be linked to differences in host socioecology and/or phylogeography. No influence of microfilarial infection on host body mass was observed. >99% sequence identity of filariae from lemur hosts of different genera.